The Effectiveness of Using Microsoft Sway Application on Improving Social Studies Learning Outcomes of Seventh-Grade Students at SMPN 5 Panca Rijang - Fitriya Kahar; Usman M Usman M; Handy Ferdiansyah; Nurmayanti Nurmayanti (Universitas Muhammadiyah Enrekang, 2025)
This study aims to determine the effectiveness of using the Microsoft Sway application in improving the learning outcomes of seventh-grade students in Social Studies (IPS) at UPT SMPN 5 Panca Rijang. The background of this research is the low achievement in Social Studies learning, caused by a lack of student interest and minimal use of varied learning media. This research employed a quantitative approach with a quasi-experimental method using a one-group pretest-posttest design. The sample consisted of all 35 seventh-grade students. Data were collected through documentation and objective tests in the form of multiple-choice questions. The results showed that the average pretest score of 49.42 increased to 81.14 in the posttest. The N-Gain analysis showed a score of 66.47%, categorized as “moderately effective.” Based on these findings, it can be concluded that the use of Microsoft Sway is effective in enhancing students’ Social Studies learning outcomes. This study recommends integrating Microsoft Sway into classroom instruction as an alternative technology-based interactive learning medium.